AB0623 ANTI-NEUTROPHIL CYTOPLASMIC ANTIBODY-ASSOCIATED VASCULITIS AND RISK OF CEREBROVASCULAR ACCIDENT: A SYSTEMATIC REVIEW AND META-ANALYSIS. (June 2019) - Ungprasert, Patompong; Wijarnpreecha, Karn; Cheungpasitporn, Wisit
Abstract : Background: An increased risk of cardiovascular disease, including cerebrovascular accident (CVA), among patients with chronic inflammatory immune-mediated disorders is well-recognized, especially among patients with rheumatoid arthritis and systemic lupus erythematosus [1]. Patients with anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) may be at an increased risk of CVA as well although the data are still inconclusive as most studies addressing this association were small in size. Objectives: The current systematic review and meta-analysis was conducted with the aims to comprehensively identify all relevant studies and summarize their results together to better characterize the risk of CVA among patients with aAV. Methods: Two investigators independently searched for published studies indexed in MEDLINE and EMBASE database from inception to October 2018 using the search strategy that included the terms for anti-neutrophil cytoplasmic antibody-associated vasculitis and cerebrovascular accident. Eligible studies must be cohort studies (either retrospective or prospective) that compared the risk of incident CVA between patients with aAV and individuals without aAV. They must also report the relative risk or hazard ratio with 95% confidence interval (CI) of this comparison. Point estimates and standard errors from each study were extracted and combined together using the random effect, generic inverse variance technique of DerSimonian and Laird. Results: A total of 5 studies fulfilled the inclusion criteria and were included in this meta-analysis. The risk of incident CVA among patients with aAV was significantly higher than individuals without aAV with the pooled risk ratio of 1.49 (95% CI, 1.06–2.10). The statistical heterogeneity was insignificant with an I 2 of 11%. The forest plot of this meta-analysis is shown as figure 1 . The funnel plot of this study was relatively symmetric and did not suggest the presence of publication bias. Conclusion: A significantly increased risk of CVA among patients with aAV was demonstrated by this meta-analysis. Physicians who take care of patients with aAV should be aware of this risk and focus on interventions to modify other conventional risk factors for CVA may be warranted. References: [1] Hintenberger R, et al. Cardiovascular disease in patients with autoinflammatory syndromes. Rheumatol int. 2018;38:37-50. Disclosure of interests: None declared